2017
DOI: 10.1371/journal.pone.0185796
|View full text |Cite
|
Sign up to set email alerts
|

Beta-arrestin 1 regulation of reward-motivated behaviors and glutamatergic function

Abstract: The two highly homologous non-visual arrestins, beta-arrestin 1 and 2, are ubiquitously expressed in the central nervous system, yet knowledge of their disparate roles is limited. While beta-arrestin 2 (βarr2) has been implicated in several aspects of reward-related learning and behavior, very little is known about the behavioral function of beta-arrestin 1 (βarr1). Using mice lacking βarr1, we focused on the role of this scaffolding and signal transduction protein in reward-motivated behaviors and in striatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…The down-regulation of the arrestin pathway at 18°C and 34°C could provoke alterations of ZF cognitive abilities in analogy to β arrestin 1 KO-mice that showed deficits in learning tasks suggesting spatial learning deficiencies and general alteration in reward processing [76].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The down-regulation of the arrestin pathway at 18°C and 34°C could provoke alterations of ZF cognitive abilities in analogy to β arrestin 1 KO-mice that showed deficits in learning tasks suggesting spatial learning deficiencies and general alteration in reward processing [76].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The researcher observed that self-administration of cocaine augmented the AMPA/NMDA ratio and GluN2B-NMDARs in spinal medium neurons of WT mice. But for KO spinal medium neurons, an increase in AMPA/NMDA ratio was detected accompanied by fewer GluN2B-NMDARs and a presence of calcium-penetrable AMPARs [8]. The study suggested that ifenprodil is an inhibitor of NMDA receptor specifically of glycine-binding NMDA receptor (GluN1) and glutamate-binding NMDA receptor subunit 2 (GluN2B) [10].…”
Section: Editorialmentioning
confidence: 88%
“…In a study, Mittal et al examined the key mechanisms involved in behavioural performances mediated by β-arrestin 1 [8]. Using a mice model lacking β-arrestin 1, they studied the role of this scaffolding protein in reward-driven behaviours and striatal glutamatergic role.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations